Polymorphous Adenocarcinoma at Rare Locations: A Series of Two Cases - Rajpoot, Jyoti; Pujani, Mukta; Agarwal, Charu; Jain, Manjula; Goyal, Himani; Sarohi, Monica; Sashidharan, Jaseetha (International Journal of Human and Health Sciences (IJHHS), 2024)
Polymorphous adenocarcinoma (PAC) is a slowly growing malignant minor salivary gland tumor with a very low risk of recurrence and distant metastases. PAC is characterized by cytologic uniformity and architectural diversity. Various morphologic patterns include papillary, tubular, reticular, solid, cribriform, and single-file patterns. A very less percentage of cases have been reported in the nasal cavity and parotid. On cytology, smears are cellular with tumor cells are uniform and arranged in the form of clusters, papillae and singly scattered. We present here two cases, one case in the parotid reported on cytology and later confirmed on histopathology and the other case in the nasal cavity reported on biopsy, of which we later also received the resection specimen. Polymorphous adenocarcinoma is a slow-growing malignancy with an excellent prognosis. Though, it rarely occurs in the nasal cavity and parotid gland but it should be kept among differential diagnoses. Histopathology is the gold standard to diagnose salivary gland tumors but Immunohistochemistry is a useful aid in ruling out close differentials. Surgical excision is the main modality of treatment with excellent disease-specific survival. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 297-301